Are Children's Hospitals Unique in the Community Benefits They Provide? Exploring Decisions to Prioritize Community Health Needs Among U.S. Children's and General Hospitals - Franz, Berkeley; Cronin, Cory E. (Frontiers in Public Health, 2020)
The Affordable Care Act expanded community benefit requirements for nonprofit hospitals, which now must demonstrate that they take into account the needs of their surrounding community in deciding where to make community benefit investments. No study to date has assessed the Community Health Needs Assessments (CHNAs) of a large sample of nonprofit hospitals to understand how hospitals determine the priority health needs that they include for their community or how prioritized health needs differ between general and children's hospitals. We analyzed the CHNAs of a 20% random sample of general hospitals in the United States as well as all children's hospitals. After identifying the five most common needs across all hospitals—mental health, substance misuse, social needs, chronic illness, and access to care—we used descriptive statistics and multivariate logistic regression to determine which hospitals were most likely to prioritize each of these five needs in their CHNA and the organizational, county, and regional factors associated with prioritizing a need. We found that children's hospitals were more likely than general hospitals to prioritize each of these five needs in their CHNA and that related county-level health indicators were significantly associated with hospitals prioritizing social needs and substance misuse as top needs in their CHNAs. County-level demographic variation, such as the percentage of white residents, and regional location were significantly related to whether hospitals prioritized a need in their CHNA. Our results suggest that children's hospitals are more likely to include a similar list of health issues on their CHNAs and that factors beyond county-level health indicators (e.g., organizational mission, regional health indicators, etc.) are operative in hospital decisions to include needs on their CHNAs.